Thailand Award for the Best International Invention & Innovation in Seoul International Invention Fair 2019, South Korea : Smart Knock-down Fish Farming - Saiful Bahari, Hj Mohd Yusoff; Ibrahim, Zalina (National Research Council of Thailand, 2019)
Smart Knock-down Fish Farming is a product that house different kind of fishes based on species. The product consider the nature of the fish and able to be flat packed for transporting products especially to the rural area.